TANGGUNGJAWAB NEGARA TERHADAP KEBAKARAN HUTAN DAN LAHAN DALAM PERSPEKTIF HUKUM NASIONAL DAN ISLAM - Syafi’ul Anam; Muhammad Afdhal Askar (Institut Agama Islam Negeri Batusangkar, 2020)
The responsibility given by the state to the occurrence of forest and land fires so far has not been considered optimal. Whereas the state has responsibilities towards its citizens, one of which is in ensuring the rights of citizens to get a clean and healthy environment. The liability referred to arises from the legal relations between the countries as mentioned in the fourth alinia of the Preamble of the 1945 Constitution through the phrase